Healthcare Access and Regional Inequalities as Determinants of Childhood Stunting in East Nusa Tenggara, Indonesia: A Systematic Review - Arif Andriyanto; Ardian S. Leky (Universitas Ahmad Dahlan, 2026)
Background: Stunting remains a major public health problem in Indonesia, particularly in East Nusa Tenggara (NTT) Province, which has the highest prevalence of stunting nationally. The high incidence of stunting in NTT is influenced not only by inadequate nutrition but also by limited access to health services, clean water, and sanitation, as well as socioeconomic and development disparities between regions. Method: This study employed a systematic review method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A systematic literature search was conducted through Google Scholar, PubMed, and Garuda databases using the keywords